O processo de avaliação da cultura corporal realizada por professores de educação física do Ensino fundamental – Anos iniciais – do município de Assis Chateaubriand – PR - Baliero, Franciele Fernandes (2015)
This dissertation has as subject-matter the avaliation process of learning made by Physical Education teachers – first years – on Assis Chateaubriand city. Such tematic aims to analyse these teachers’ enunciations related to the aspects of this critical point of the education process. The general objective was to search for the comprehension through the analysis along with the bakhtinian notions of Dialogism, Polyphony and Heteroglossia. The specific objectives were: to detach the evaluation’s concepts and Physical Education of the statements; to verify the procedures adopted by the Physical Education teachers on the accomplishment of the learning evaluation; and to apprehend the teachers’ perception about the importance of the Physical Education on the general development of the students. A research was made in order to accomplish the proposed objectives, oriented by the bakhtinian perspective of language (and by other theoreticians that broach the same subject), such as Aranha (2007), Bakhtin (2003), Bakhtin/Volochinov (2004), Fiorin (2003 e 2006) and Brait (2007, 2008 and 2009), besides being oriented by other theoreticians that deal with Physical Education and school evaluation: Soares et all (2009), Darido (2008; 2012 e 2014), Luckesi (2002) and Castellani Filho (2001). Meanwhile, the instruments used for the research were semistructured interviews and to help on the analysis was used Bardin (2009). All the 17 Physical Education teachers who work on Assis Chateaubriand city were interviewed in March and April, 2014. After the analysis of the enunciations obtained with the interview guide, it was possible to realize the voices that interpenetrate these teachers’ speeches. Voices that shape the pedagogical practice of the teachers and that are a result of a whole historical process made from their academic background, from difficulties faced at schools, from the relationship with their pairs, etc. Trying to visualize this perspective allowed pointing out that this subject that teaches Physical Education seems not to be properly prepared, in other words, it lacks both theorical and practical knowledge